Sintren in Gender Expressivity: The Role of Women in Dance Traditions - Precillia, Monita; Cahyani, Magfi Redia; Jaeni, Jaeni (Gondang: Jurnal Seni dan Budaya, 2024)
The Study of Sintren in Gender Expressivity: The Role of Women in Dance Traditions analyzes the role of Cirebonese women in expressing and preserving the art of Sintren. This research aims to further analyze and examine how women contribute to the arts and culture of Cirebon. A qualitative, empirical approach was employed, involving diverse documentation of events, recordings of speech, words, and gestures of the subjects, specific behaviors, written documents, and various visual images related to the social phenomenon. The study employs five stages of qualitative research methods, namely: (1) participant observation, (2) conversation analysis, (3) discourse analysis, (4) content analysis, and (5) ethnographic data collection. The findings reveal that, in a broader social context, the role of women in Sintren dance reflects societal changes. Although Sintren remains deeply rooted in tradition, women involved in its practice have begun exploring new aspects, such as innovations in movement and interpretation. These changes demonstrate that women are not merely passive participants in tradition but actively contribute to enriching and developing the performing arts. This creates a space for dialogue between tradition and modernity, providing women with opportunities to express their identities in a broader context. The study concludes that Sintren is an art form closely linked to the mystical and cultural practices of the Cirebon community. However, in the modern era, Sintren is increasingly marginalized amidst the advancements of the times. This is evident in the limited studies on Sintren, the scarcity of its documentation, and its performances being limited to specific groups. Such conditions highlight the need for greater efforts in preserving and revitalizing this traditional art form.